Ethnobotanical Survey Of Medicinal Plants In Tribal Regions Of India - Dr Tejaswini Prasad Babar; Dr. Vinod Kumar Jain; Dr Tulika Mishra; Dr.Devidas Narhar Patil (Revista Electronica de Veterinaria, 2024)
The tribal communities of India harbor an extensive and unique knowledge of medicinal plants, passed down through generations and deeply intertwined with their cultural heritage. This ethnobotanical survey investigates the medicinal plants used by various tribal groups across India, aiming to document the species, their local names, parts used, preparation methods, and therapeutic applications. The study employed field surveys, interviews with traditional healers, and an in-depth review of ethnobotanical literature to capture the rich tapestry of plant-based knowledge that continues to play a crucial role in tribal healthcare systems. More than 100 plant species were identified, each with specific uses ranging from common ailments like fever and digestive disorders to more complex conditions such as diabetes, malaria, and inflammatory diseases. The findings underscore the critical role of traditional healers who utilize these plants in their day-to-day medical practices, often blending rituals and spiritual beliefs with physical treatments. The study also highlights the cultural and ecological importance of these medicinal plants, revealing how their use is not just about health but is also deeply connected to the tribes’ spiritual beliefs and way of life. Despite the rich diversity of this knowledge, there are growing concerns over its survival, as rapid modernization, habitat loss, and diminishing interest among younger generations threaten to erode this invaluable cultural asset. The survey calls attention to the urgent need for conservation efforts that protect both the plants and the traditional knowledge systems that sustain them. Additionally, it advocates for the integration of this indigenous wisdom into mainstream medicine, promoting sustainable utilization and the potential development of novel therapeutic agents. By documenting the ethnobotanical practices of tribal communities, this study aims to provide a foundation for future research in pharmacognosy, conservation, and the sustainable development of plant-based medicines. It also emphasizes the importance of protecting indigenous knowledge rights and ensuring that tribal communities benefit from the use and commercialization of their traditional resources. Ultimately, this paper seeks to illuminate the vast potential of tribal ethnobotany in addressing contemporary health challenges and contributing to global medicinal plant knowledge.